Comparison of the HYSIM and the tank models in Cho Shui river basin, Taiwan - A.F.M. Afzal Hossain, (1989)
The Cho Shui river Basin is the second largest basin of Taiwan. To conduct the optimum water resources, utilization study for the basin daily flow data are developed using mainly two models e.g. the HYSIM (Hydrologic Simulation Model), and Tank Model. Both models applied are of rainfall runoff type. The HYSIM model has been applied to ten gauged sites, which is calibrated for short period of record and then daily flow data for 28-years are developed. During calibration more weightage is given on low flows. Tank model latest version is applied to four basins out of the ten. It is observed from the statistical comparison and matching of hydrographs that the results from the HYSIM model are better than that of Tank Model in those four stations